PERANAN KELEMBAGAAN POSDAYA DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI DESA TOLITE JAYA KECAMATAN TOLINGGULA KABUPATEN GORONTALO UTARA - Harun, Isra; Baderan, Umar Sako; Paramata, Sri Hantuti (JSAP : Journal Syariah and Accounting Public, 2019)
This study aims to obtain a description of the institutional of Posdaya in increasing the income of the community in Tolite Jaya Village, Tolinggula Sub District, North Gorontalo District. The research method used qualitative type. Data collection techniques are done through interviews, observation and documentation. The result of the research shows the role of institutional posdaya in improving the family welfare in Tolite Jaya Village Tolinggula Sub District, North Gorontalo regency. The role of Posdaya in Tolite Jaya Village in giving aid is only in the form of money, but there are groups that do not receive the aid because they have not paid. The role of institutional posdaya through the involvement of all parties with the involvement of village governments and members of the established groups. The mechanism of Posdaya institutional work in Tolite Jaya Village is in accordance with the proposed form of assistance.